EDUCATION CURRICULUM FOR SOCIETY 5.0 IN THE NEXT DECADE - Usmaedi, Usmaedi (Jurnal Pendidikan Dasar Setiabudhi, 2021)
Industry 4.0 has become a major revolution in the development of human life. Digital technology has influenced humans in various ways from economic, social, political and even in human life itself. Society 5.0 places more emphasis on efforts to place humans as the center of innovation (human centered) while technological advances are utilized to improve the quality of life, social responsibility and develop sustainability. This research is a qualitative research with literature study method. This method collects information or data through books, journals or articles that are relevant to the issue being studied. Society 5.0 emerged as a development of the industrial revolution 4.0 which was considered to have the potential to degrade the role of humans themselves. In society 5.0, humans will be the center (human centered) while remaining technology-based. The emergence of society 5.0 requires patented breakthroughs in an effort to face the challenges that will be posed by society 5.0. The existence of society 5.0 poses its own challenges in various fields of life, one of which is in the field of education, including learning. To deal with the complexities of living conditions in the Society 5.0 era, students are not sufficiently equipped with the ability to read, write and count or better known as "Tree R" (reading, writing, arithmetic), but also need to be equipped with global community competencies or also called skills. ababd 21, namely the ability to communicate, be creative, think critically, and collaborate or known as the "Four Cs", namely communicators, creators, critical thinkers, and collaborators. Keywords: Industry 4.0, Society 5.0, Educational Transformation Abstrak Industri 4.0 telah menjadi sebuah revolusi besar dalam perkembangan kehidupan manusia. Teknologi digital telah mempengaruhi manusia dalam berbagai hal dari ekonomi, sosial, politik dan bahkan dalam kehidupan pribadi manusia itu sendiri. Society 5.0 lebih menekankan pada upaya menempatkan manusia sebagai pusat inovasi (human centered) adapun kemajuan teknologi dimanfaatkan untuk meningkatkan kualitas hidup, tanggung jawab sosial dan berkembang keberlanjutan. Penelitian ini merupakan penelitian kualitatif dengan metode study literature. Metode ini mengumpulkan informasi atau data melalui buku, jurnal atau artikel yang relevan dengan isu yang sedang dikaji. Society 5.0 muncul sebagai pengembangan dari revolusi industri 4.0 yang dinilai berpotensi mendegradasi peranan manusia itu sendiri. Dalam society 5.0, manusia akan menjadi pusatnya (human centered) dengan tetap berbasis teknologi (technology based). Munculnya society 5.0 dibutuhkan terobosan-terobosan yang paten dalam upaya menghadapi tantangan yang akan ditimbulkan society 5.0. Adanya society 5.0 menimbulkan tantangan tersendiri dalam berbagai bidang kehidupan, salah satunya adalah dalam bidang pendidikan, termasuk dalam pembelajaran. Untuk menghadapi kompleksitas kondisi kehidupan masyarakat era Society 5.0, peserta didik tidak cukup dibekali dengan kemampuan membaca, menulis dan berhitung atau lebih dikenal dengan sebutan â€œTree Râ€ (reading, writing, arithmetic), tetapi juga perlu dibekali kompetensi masyarakat global atau juga disebut kecakapan ababd 21, yakni kemampuan berkomunikasi, kreatif, berpikir kritis, dan berkolaborasi atau dikenal dengan sebutan â€œFour Csâ€, yaitu communicators, creators, critical thingkers, and collaborators. Kata kunci: Industri 4.0, Society 5.0, Transpormasi Pendidikan